Comparison of two molecular assays for detection and characterization of Aspergillus fumigatus triazole resistance and Cyp51A mutations in clinical isolates and primary clinical samples of immunocompromised patients - Postina, Patricia Amely Elisabeth; Boch, Tobias; Skladny, Julian; Miethke, Thomas; Merker, Natalia; Hofmann, Wolf-Karsten; Buchheidt, Dieter; Spiess, Birgit (Frontiers in microbiology, 2018)
In hematological patients, the incidence of invasive aspergillosis (IA) caused by azole resistant As-pergillus fumigatus (ARAf) is rising. As the diagnosis of IA is rarely based on positive culture in this group of patients, molecular detection of resistance mutations directly from clinical samples is crucial. In addition to the in-house azole resistance ARAf polymerase chain reaction (PCR) assays detecting the frequent mutation combinations TR34/L98H, TR46/Y121F/T289A and M220 in the Aspergillus fumigatus (A. fumigatus) Cyp51A gene by subsequent DNA sequence analysis, we investigated in parallel the commercially available AsperGenius® real time PCR system in detecting the Cyp51A alterations TR34/L98H and Y121F/T289A directly from 52 clinical samples (15 biopsies, 22 bronchoalveolar lavage (BAL), 15 cerebrospinal fluid (CSF) samples) and ARAf isolates (n=3) of im-munocompromised patients. We analyzed DNA aliquots and compared both methods concerning amplification and detection of Aspergillus DNA and Cyp51A alterations. As positive control for the feasibility of our novel Y121F and T289A PCR assays, we used two A. fumigatus isolates with the TR46/Y121F/T289A mutation combination isolated from hematological patients with known Cyp51A alterations and a lung biopsy sample of a patient with acute myeloid leukemia (AML). The rate of positive ARAf PCR results plus successful sequencing using the ARAf PCR assays was 61 % in biopsies, 29 % in CSF, 67 % in BAL samples and 100 % in isolates. In comparison the amount of positive PCRs using the AsperGenius® assays was 47 % in biopsies, 42 % in CSF, 59 % in BAL samples and 100 % in isolates. Altogether 17 Cyp51A alterations were detected using our ARAf PCRs plus DNA sequencing and therefrom 10 alterations also by the AsperGenius® system. The comparative evaluation of our data revealed that our conventional PCR assays are more sensitive in detecting ARAf in BAL and biopsy samples, whereby differences were not significant. The advantage of the AsperGenius® system is the time saving aspect. We consider non-culture based molecular detection of Aspergillus triazole resistance to be of high epidemiological and clinical relevance in patients with hematological malignancies.
Gesehen am 23.04.2018